Penerapan Media Animasi Dalam Pembelajaran PAK Terhadap Minat Siswa Kelas VII SMP Negeri 3 Lintongnihuta Tahun Pembelajaran 2023/2024 - Imma Suryani Berutu; Risden Anakampun; Andar G. Pasaribu (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this research is to determine the effect of applying animation media in PAK learning on the learning interest of class VII students at SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year. The research method used is a quantitative research method and a pre-experimental design research type in the form of a One Shot Case Study. The population is all class VII students of SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year, totaling 168 people and a research sample of 32 people was determined using the nonprobability sampling technique, namely Purposive Sample. Data was collected using a positive closed questionnaire with 36 items, namely 15 items for variable ) Test analysis requirements: a) positive relationship test obtained by rxy = 0.555 > rtabel rtabel(=0,05,n=32)= 0.349. b) Testing a significant relationship obtained tcount = 3.653 > > ttabel(=0,05,dk=n-2=30)= 2.042. 2) Influence test: a) Regression equation test, obtained regression equation. b) Regression coefficient of determination test (r2) = 30.8%. 3) Test the hypothesis using the F test to obtain Fcount > Ftabel= Ftabel= (=0,05,dk numerator k=14,dk denominaror =n-2=32-2=30) namely 13.34 > 2.01. Thus, Ha, that is, there is an influence of animation media in PAK learning on the learning interest of class VII students at SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year is accepted and H0 is rejected.